Primary Literature in the Undergraduate Immunology Curriculum: Strategies, Challenges, and Opportunities - Rawlings, Jason S. (Frontiers in Immunology, 2019)
Immunology is a rapidly advancing and expanding field that is regularly highlighted in the lay media, whether it be checkpoint blockade immunotherapy winning the Nobel Prize, CAR-T cells in the treatment of cancer, or the latest anti-inflammatory/immunomodulatory medication advertised directly to consumers. Advances such as these not only transform the way we think about immunology, they also illuminate how knowledge of the immune system can be harnessed to impact public health. Immunology is also a vast subject, with thousands of articles published each year that contribute to our understanding of complex processes such as inflammation, pathogen recognition, and self-tolerance. Taken together, these observations pose significant challenges to teaching immunology in the undergraduate classroom. To meet this challenge, instructors can use primary literature as a means to introduce cutting-edge discoveries that have not yet found their way into textbooks, link what students are learning to what they are exposed to in lay media, and ultimately provide added depth to the students’ understanding of the immune system. Furthermore, the addition of primary literature to the curriculum can enhance student enthusiasm for learning immunology and can provide an excellent platform for students to gain critical thinking and analytical skills. Presented here are strategies, challenges, and opportunities in the use of primary literature to effectively augment the immunology curriculum in the undergraduate classroom. Topics include selecting papers to read, teaching students how to read scientific literature, and maximizing learning outcomes.